The Stratton-Chu Integral with a Rough Facet Formulation for All-Scale Radar Sounder Simulations: Assessment with Reflectometry - Gerekos, Christopher; Haynes, Mark; Grima, Cyril; Blankenship, Donald (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2022)
Stratton-Chu radar simulations from coarsely-resolved digital elevation models (DEMs) can be accurately handled by polynomial phase approximations on the DEM facets. However, the DEM itself is only an approximation of the real terrain: a DEM is composed of planar facets and thus displays no roughness at scales below its resolution, which has important consequences on the simulated radargrams. To solve this problem, we have recomputed the linear phase approximation integral on a perturbed facet. We demonstrate the gain of fidelity over smooth-facet simulations by comparison with a real radargram. For the first time, we also apply reflectometry techniques to these simulated data, and compare it with the original output.